Analisis Ekologi dan Kelimpahan Ikan Karang Di Perairan Teluk Depapre, Kabupaten Jayapura - Matias Dimara; Baigo Hamuna; John Dominggus Kalor; Yunus Pajanjan Paulangan (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2020)
Coral fish is one of the organisms associated with the most coral reefs and is a large organism that can be found in all coral reef habitats. This study aims to determine the diversity of reef fish, community structure, and abundance of reef fish in the Depapre Bay Waters, Jayapura Regency. This research was conducted from September to October 2017 in Serebo and Kampung Tua waters. The method used is the Underwater Visual Census method at a depth of 3 to 5 m with a transect length of 75 m and an observation width of 5 m. A total of 69 species of reef fish found at the study site consisted of 16 reef fish families. The number of reef fish species at Serebo and Kampung Tua stations is 47 species and 38 species, respectively. The diversity index of reef fish ranged from 2.8264 to 2.9615 which was classified in the medium category. The uniformity index ranges from 0.7341 to 0.8142, which indicates that the community is relatively stable. The dominance index at Serebo Station is classified as high (1.00) which indicates that there are certain species (Pomacentrus mollucensis) that dominate, while at Kampung Tua station there are no specific species that dominate with a dominance index value of 0.3256. The abundance of reef fish at Serebo station was higher at 1.8347 ind/m2 than the abundance of reef fish at Kampung Tua station which was 0.5973 ind/m2. The highest abundance of reef fish species at Serebo station was Pomacentrus mollucensis (0.3647 ind/m2), while at Kampung Tua station was Ctenochaetus striatus (0.1333 ind/m2).Keywords: Reef fish; Coral reef; Underwater Visual Census; Community structure; Depapre Bay